AGROTOURISM AS FACTOR PRESERVATION OF CULTURAL HERITAGE ISSYK KUL REGION INNOVATION TRADITION - Borubaeva I. I.; Ibraimova G. T.; Abytaeva U. T.,; Mambeteminova Ch. B. (Vestnik Issyk-Kulʹskogo universiteta)
The article discusses the role of agrotourism in preserving and transmitting the cultural heritage of Kyrgyzstan. The authors analyze the impact of agrotourism on preserving traditional practices and customs of the Kyrgyz people, and also consider innovative approaches to the development of this sector. The article discusses the basic principles of agrotourism, its impact on the economy and socio-cultural sphere of the region, and offers recommendations for improving this area, taking into account traditions and modern challenges. Agritourism combines several types of travel at once: - ecotourism, - rural tourism, - ethnotourism, - culinary tourism, - geotourism, - country recreation. At the present stage of development, tourism occupies one of the promising positions in the economy of the regions of Kyrgyzstan. It acts as an incentive for the comprehensive improvement of many industries: communications, transport infrastructure, construction, agriculture, etc. The article also discusses the experience of developing agrotourism in Italy, Spain, France, Greece - as the main trendsetters in the segment of world rural tourism. The results of the study can be useful for both the academic community and practitioners in the field of tourism and cultural heritage.